2013
DOI: 10.1523/jneurosci.3200-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Hypocretin/Orexin Neurons Contribute to Hippocampus-Dependent Social Memory and Synaptic Plasticity in Mice

Abstract: Hypocretin/orexin (Hcrt) neurons in the lateral hypothalamus project throughout the brain, including to the hippocampus, where Hcrt receptors are widely expressed. Hcrt neurons activate these targets to orchestrate global arousal state, wake-sleep architecture, energy homeostasis, stress adaptation, and reward behaviors. Hcrt has recently been implicated in cognitive functions and social interaction. Here, we tested the hypothesis that Hcrt neurons are critical to social interaction, particularly social memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
104
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 64 publications
6
104
1
Order By: Relevance
“…Orexin-containing neurons project widely to many brain areas, including the VTA, NAc and the amygdala Borgland et al 2006;Yang et al 2013). It was found that the CPP associated with morphine, cocaine or food activated the hypothalamic orexin neurons (Harris et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Orexin-containing neurons project widely to many brain areas, including the VTA, NAc and the amygdala Borgland et al 2006;Yang et al 2013). It was found that the CPP associated with morphine, cocaine or food activated the hypothalamic orexin neurons (Harris et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TDW is distinguished from other states by its neuromodulatory signature, of which elevated Hcrt is a component, as Hcrt is maximally released in active waking (36) and by the θ/fast-γ oscillatory network activity we use to define it, and which in baseline nonredundantly depends on Hcrt. Hcrt signaling was shown to mediate synaptic plasticity in some contexts (74) and may also play a role in gating synaptic homeostatic events. Hence, testing Hcrt's potential role in synaptic homeostatic processes is a prerequisite for interpreting the above experiment.…”
Section: Tdw State Heterogeneity: Hcrt Loss Finely Alters the Tdw Oscmentioning
confidence: 99%
“…Abnormal social novelty recognition usually results from a deficit in social memory (17,18). We used a modified four-trial social memory assay (16,19) to explore whether Prex1 −/− mice showed impaired social learning and memory in re-recognizing the first stranger (stranger 1) (Fig.…”
Section: Significancementioning
confidence: 99%